Anonymous Survey As A Method Of Bullying Detection Among Medical Workers - Sydorenko, Anastasiia (Psychiatry, Neurology and Medical Psychology, 2017)
A literature review of the prevalence, causes and consequences of bullying in medicine was highlighted in the article. The paper stressed that bullying in medicine is a widespread phenomenon regardless of country mentality and economic development and occurs in hospitals around the world. The study presented a special questionnaire for anonymous bullying detection which includes 16 questions, answers to which highlight detailed circumstances of bullying phenomenon among medical workers and show which category of persons are often suffering from harassment. Six topics for an educational module for doctors at all levels are proposed in the article in order to improve communication and establish a friendly atmosphere in the team. The author also draws the reader’s attention to the need for a special ethics committee creation that would have contributed to greater impartiality and objectivity in resolving bullying cases